2004
DOI: 10.1016/j.jom.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and coordination in make‐to‐order supply chains

Abstract: This research, based on our observations of an industrial vendor-manufacturer relationship, investigates the impact of information sharing and physical flow coordination in a make-to-order supply chain. We mathematically model and develop simulation-based rolling schedule procedures for analyzing the manufacturer's ordering policies, transportation activities, and the vendor's manufacturing and order fulfillment processes under five alternative integration strategies. Our objective is to measure the value of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
194
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(217 citation statements)
references
References 34 publications
2
194
1
6
Order By: Relevance
“…Sezen (2008) findings endorse the relevance of the practice in influencing another operational performance attribute (flexibility), especially in variable uncertain delivery and demand environments. Many other studies indicate that cooperative information sharing among SC members en hances the effectiveness and competitiveness of the SC, by enabling actors to incorporate necessary information into their work (Sahin, Robinson 2005;Li et al 2006). Studies indicated that coordinated sharing of supply and demand information with SC partners reduced cost and shortened order cycle time (Strader et al 1999), increase in informa tion sharing amidst volatile demand environment led to better SC responsiveness (Lee et al 2000) and enhanced operation, product and delivery flexibility (Sezen 2008).…”
Section: Supply Chain Information Access and Value Co-creationmentioning
confidence: 99%
“…Sezen (2008) findings endorse the relevance of the practice in influencing another operational performance attribute (flexibility), especially in variable uncertain delivery and demand environments. Many other studies indicate that cooperative information sharing among SC members en hances the effectiveness and competitiveness of the SC, by enabling actors to incorporate necessary information into their work (Sahin, Robinson 2005;Li et al 2006). Studies indicated that coordinated sharing of supply and demand information with SC partners reduced cost and shortened order cycle time (Strader et al 1999), increase in informa tion sharing amidst volatile demand environment led to better SC responsiveness (Lee et al 2000) and enhanced operation, product and delivery flexibility (Sezen 2008).…”
Section: Supply Chain Information Access and Value Co-creationmentioning
confidence: 99%
“…Sahin and Robinson (2005) also considered that the more complete the information sharing is, the more the cost can be reduced without inventory risks through joint planning by suppliers and manufacturers. Moreover, by following such policies collaborative planning and execution, such as the coordination of purchasing, manufacturing and product delivery, can be implemented efficiently among supply chain partners.…”
Section: Introductionmentioning
confidence: 99%
“…Through information sharing among all the partners in a supply chain, the upstream material suppliers are be able to modify their production strategies from make-to-order to make-to-stock after obtaining figures on future demand from the downstream retailers. Additionally, the suppliers' batching delivery strategies can also be formulated so that the delivery date can reduce the total cost for the downstream retailers, since it can mitigate the bullwhip effect and achieve better performance (Sahin and Robinson, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahin and Robinson Jr. (2005) evaluated different strategies in the make-to-order environment: four with none or partial information sharing, with none or partial coordination, and one with full information sharing and full coordination. For various data parameters, i.e.…”
Section: Introductionmentioning
confidence: 99%